Designing Hotel and Tourism Area in Puncak Sidiangkat Dairi with Ecovillage Design Approach - Tresia Martina Manalu; Beny OY Marpaung (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2026)
Dairi Regency is known as a regency that has a natural charm that can be a potential attraction that can attract many tourists. Puncak Sidiangkat is one of the destinations that is often visited because of its natural beauty which is still very beautiful and green. So this research was conducted with the aim of planning hotels and tourist areas using ecovillage design. Puncak Sidiangkat which has the opportunity to build hotels and glamping along with other tourist facilities, develops knowledge about the advantages of natural resources in Dairi Regency which blends directly with nature in an effort to achieve economic sustainability. The design of hotel and tourist areas is inseparable from how to design buildings that have a positive effect on the surrounding environment, especially the development of mountain tourism infrastructure and facilities as an environmentally friendly and energy-efficient tourism sector. This study also considers local cultural values, community participation, and the use of sustainable materials to ensure long-term environmental balance. Furthermore, the integration of renewable energy systems, proper waste management, and landscape conservation is emphasized to support eco-friendly tourism development. Through this approach, the project is expected to enhance tourist experience while preserving natural resources and improving the local economy.